A SURVEY OF THE ENGLISH READING HABITS OF EFL STUDENTS IN INDONESIA - Erna Iftanti (TEFLIN, 2012)
This article investigated the English reading habits of Indonesian students of EFL. The data were collected through a questionnaire survey and interview validation. The questionnaires were distributed to 546 EFL college students in East Java. Based on the statistical analysis of the data, it is concluded that although the students have read English since elementary school, they do not indicate to have good English reading habits. Only few of them are identified to have good English reading habits as suggested by their eagerness to regularly spend time reading various types of English texts and their high motivation to read English for pleasure. The EFL students read English for some purposes, i.e. for school assignments, for pleasure, and for knowledge and English skills improvement. Their positive belief about reading does not motivate them to read English for pleasure; rather, it is school assignments that appear to be their biggest motivation.